A two-sided collaborative transparent display supporting workspace awareness. Issue 101 (May 2017) - Li, Jiannan; Greenberg, Saul; Sharlin, Ehud
Abstract: Transparent displays naturally support workspace awareness during face-to-face interactions. Viewers see another person's actions through the display: gestures, gaze, body movements, and what one is manipulating on the display. Yet we can design even better collaborative transparent displays. First, collaborators on either side should be able to directly interact with workspace objects. Second, and more controversially, both sides should be capable of presenting different content. This affords: reversal of images/text in place (so that people on both sides see objects correctly); personal and private territories aligned atop each other; and GUI objects that provide different visuals for feedthrough vs. feedback. Third, the display should visually enhance the gestural actions of the person on the other side to better support workspace awareness. We show how our FacingBoard-2 design supports these collaborative requirements, and confirm via a controlled study that visually enhancing gestures is effective under a range of deteriorating transparency conditions. Graphical abstract: Highlights: Theory, design rationale and requirements for the design of a two-sided transparent display that affords collocated collaboration. Implementation and technical description of a novel two-sided transparent display that satisfies the above requirements. Study of the nuances of using such a display, with particular attention paid to maintenance of workspace awareness.